Dataset for PLOS NTD paper 'Endothelial and Inflammatory Pathophysiology in Dengue Shock: insights from a prospective cohort study in Vietnam' - McBride, A (University of Oxford, 2024)
Clinical and biomarker data gathered between 2019-2022 for the PhD of Angela McBride, funded by Wellcome Trust.